Shades of Manipulation: A Large-Scale Analysis of Deceptive Design in Brazilian Mobile Applications - Coelho, Amanda; Lima, Gabriel; Melo, Lucas; Ribeiro, Levi de Brito; Darin, Ticianne (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2025: Anais do XXIV Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2025)
Introduction: Interfaces with Deceptive Patterns (DPs) manipulate users against their best interests, but most Human-Computer Interaction research about DPs focuses on WEIRD context (Western, Educated, Industrialized, Rich, and Democratic). Objective: This study looks at the Global South, specifically identifying, quantifying, and classifying the prevalence of DPs in 100 popular mobile applications in Brazil, and contrasting it with two high-income countries. Methodology: We analyzed DP classes in 100 popular mobile applications in Brazil from nine categories. Results: DPs presence (96%) and average (7.51) are comparable across countries, but their distribution greatly differs. We discuss how these results relate to the different socio-cultural contexts, the particular use cases in Brazil, and their impact.